(untitled) (Modern information system and technologies, 2018)
The great desire of every person to achieve maximum comfort in each of the spheres of life has also affected the international Internet web: due to the increased variety of technical facilities and the expansion of the service package. Accordingly, it is possible to increase the efficiency of spending time on the Internet by providing access to users to specialized applications developed on the most widely distributed software.